India's Challenge to Meet the Millennium Development Goals - Nirupam Bajpai, Jeffrey D. Sachs, and Nicole Volavka (CGSD Working Paper No. 24, 2005)
On its current economic trajectory, India will achieve some of the eight Millennium Development Goals, but will miss many of the others. The good news is that India is making great strides with regard to the first of the Millennium Development Goals: reducing extreme poverty. Even though there is an active debate about the "exact" measure of extreme poverty, all indicators suggest rapid progress, enough on the current trajectory so that the headcount poverty rate in 2015 will be less than half of the rate in 1990, as called for by the Millennium Development Goals. At the same time, India is likely to miss several of the other goals, related to hunger, IMR, under-5, and MMR, disease, and the physical environment. The proportion of children in India who are chronically undernourished remains very high. So too does the MMR and IMR. And the goal of environmental sustainability is not being achieved, as parts of India are suffering from worsening crises of water, soils, and deforestation. What India requires is a significant increase of targeted investments in clinics, schools, nutrition programs, disease control, irrigation, rural electrification, rural roads, and other basic investments, especially in rural India as the current budgetary allocations are inadequate. Higher public investments in these areas need to be accompanied by systemic reforms that will help overhaul the present system of service delivery, including issues of control and oversight. Additionally, India should "plan for success." The Planning Commission should ensure that current programs as well as the next Five-Year Plan are built around achieving the Millennium Development Goals. Indeed, not only the Union Government, but every state and even every district, should base their investment programs around achieving the Millennium Development Goals